KONFLIK NORMA KEWAJIBAN NOTARIS MERAHASIAKAN AKTA DENGAN KEWAJIBAN MELAPORKAN TRANSAKSI KEUANGAN YANG MENCURIGAKAN - Yalid Yalid; Birman Simamora (Faculty of Law - Tarumanagara University, 2021)
The formulation of the problem in this study is how to resolve the conflict of norms of the obligation of notaries to keep the deed secret with the obligation to report suspicious financial transactions? The research method is carried out in literature with the type of normative legal research, according to dogmatic issues related to norm conflicts. The results showed that the conflict resolution of the norms of the obligation of notaries to keep the deed secret with the obligation to report suspicious financial transactions is a conflict of norms that can be resolved using legal principles as legal treatment, including: First, “lex superiori derogat legi inferiori”; Second, “lex specialis derogate legi generali”; Third, l”ex posteriori derogat legi priori”. Analysis of norm conflict resolution using legal preference techniques, the notary's obligation to keep the deed secret based on Article 4 paragraph (2), Article 16 paragraph (1) letter f and Article 54 paragraph (1) UUJN has legal force that cannot be defeated by the strength of Article 3 PP ML Reporters. Thus, a notary who does not report suspicious financial transactions cannot be said to have acted against the law. On the other hand, a notary is against the law if he leaks the secret of his position or opens the confidentiality of a deed based on the norms of “Article 4 paragraph (2), Article 16 paragraph (1) letter f and Article 54 paragraph (1) UUJN”.